1997
DOI: 10.1097/00005131-199702000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trauma and Pelvic Fracture on Female Genitourinary, Sexual, and Reproductive Function

Abstract: We found that pelvic trauma negatively affected the genitourinary and reproductive function of female patients. The increased rate of cesarean section in women after pelvic trauma may be multifactorial in origin and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 31 publications
4
93
0
Order By: Relevance
“…Comparing reduction quality, patients with [ 5 mm persistent displacement had more difficulty with sexual intercourse at the 6-month interval. This is consistent with previous findings [6]. No other correlation with any functional outcome measurement or return to work was observed.…”
Section: Discussionsupporting
confidence: 93%
“…Comparing reduction quality, patients with [ 5 mm persistent displacement had more difficulty with sexual intercourse at the 6-month interval. This is consistent with previous findings [6]. No other correlation with any functional outcome measurement or return to work was observed.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are similar to previous studies (Table 10) reporting rates of impotence of 11% to 30% in males [18,20,24,25,34], with higher rates in studies considering only patients with urethral rupture [2,13,15,18,26,39]. Reported rates of dyspareunia range from 2% [34] to 43% [11] in females after pelvic injury (Table 11). A study of young women after pelvic fracture reported 45% feeling less sexually attractive and 39% experiencing a decrease in sexual pleasure [27].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are supported by a previous German study [28] using the Tile classification [40], which reported higher rates of sexual dysfunction in Type B1 than B2 fractures and in Type C than B2 injuries, as well as other studies showing greater instability associated with more sexual complaints and less recovery [16,28,29,34]. However, there are conflicting reports, with other studies finding no apparent relationship of pelvic fracture type and sexual dysfunction in males [25,31] or females [3,9,11]. In contrast, men with sacroiliac fractures and women with diastasis of the pubis were reportedly at higher risk of sexual dysfunction and incontinence [43], whereas women with residually displaced pubic rami fractures experienced higher rates of urinary complaints and of dyspareunia than those without displacement [11].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations